PERUBAHAN SUARA NAPAS DAN FREKUENSI PERNAPASAN PADA KLIEN YANG MENDERITA PENYAKIT PARU OBSTRUKSI KRONIK (PPOK) DENGAN FISIOTERAPI DADA DI RSUD MARDI WALUYO KOTA BLITAR: CHANGES IN BREATHING SOUND AND BREATHING FREQUENCY OF CLIENTS WHO HAVE CHRONIC OBSTRUCTION PULMONARY DISEASE (COPD) WITH CHEST PHYSIOTHERAPY IN MARDI WALUYO HOSPITAL, BLITAR - Setijaningsih, Triana; Fazira, Giana Irda; Sepdianto, Tri Cahyo (Stikes Wira Medika Bali, 2019)
Chest physiotherapy is a nursing action performed to clean the lungs from secretions. The purpose of this study was to describe changes in breathing sounds and breathing frequency before and after chest physiotherapy. The study design used a descriptive research design with a sample of 11 people. Data collection using questionnaire sheets and observation. The results showed that the average breathing frequency in COPD patients before and after chest physiotherapy visits I to visit III decreased by 11 points, from 31x / minute to 20x / minute, and the lobe location occurred with additional breathing sounds, ronkhi before and after chest physiotherapy, on visit I to visit III it dropped by two points, from three lobes or 46% (5 patients) to one lobe, 78% (7 patients). Chest physiotherapy on being able to increase secret expenditure. The implementation of chest physiotherapy should be done 2x/day in order to obtain maximum results.